Comparative proteomics analysis of the mouse mini-gut organoid: insights into markers of gluten challenge from celiac disease intestinal biopsies - Moulder, Robert; Bhosale, Santosh D.; Viiri, Keijo; Lahesmaa, Riitta (Frontiers in Molecular Biosciences, 2024)
Organoid models enable three-dimensional representation of cellular systems, providing flexible and accessible research tools and can highlight key biomolecules. Such models of the intestinal epithelium can provide significant knowledge for the study of celiac disease and provide additional context for the nature of markers observed from patient biopsy data.Using LC-MS/MS, the proteomes of the crypt and enterocyte-like states of a mouse minigut organoid model were measured. The data were further compared with published biopsy data comparing the changes induced by gluten challenge after a gluten free diet. These analyses identified 4850 protein groups and revealed how 400 putative biomarkers of dietary challenge were differentially expressed in the organoid model. In addition to the extensive changes within the differentiated cells, the data reiterated the disruption of the crypt-villus axis after gluten challenge. The mass spectrometry data are available via the ProteomeXchange with the identifier PXD023737.